Analysis of COVID-19 Prevention Behaviour among Diabetes Mellitus Comorbidity Patients in Palembang - Giszka Putri; Hamzah Hasyim; Nur Alam Fajar (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: COVID-19 in Diabetes Mellitus (DM) patients are at higher risk for severe complications than people without DM. Preventive behaviour is the best way to avoid COVID-19 infection for DM patients due to its bad impact, such as severe symptoms requiring intensive care, leading to death. Objective: This study aims to analyse the COVID-19 preventive behaviour among DM comorbidity patients in Palembang. Method: The cross-sectional study was conducted from April 2021 to May 2021 using a questionnaire to diabetic patients at six community health centres in Palembang. The questionnaire has four sections: patient characteristics, knowledge, attitude, and COVID-19 prevention behaviour. A proportional random sampling technique was used to determine the number of samples according to the data on diabetic patients in each health centre. The total sample was 183 respondents from 1.266 total population diabetic patients in six community health centres. Respondents were diabetic patients aged ³ 18 years old and willing to fill out the questionnaire. Univariate, bivariate, and multivariate statistical analyses were used to analyse the data. Results: More respondents have good knowledge (50.3%), negative attitude (57.3%), and poor COVID-19 preventive behaviour (53.0%). The findings revealed a statistical significance between knowledge (P-value = 0.0001), attitude (P-value = 0.0001), and educational status (P-value = 0.0001) with COVID-19 preventive behaviour. Furthermore, knowledge is the most determinant factor of COVID-19 preventive behaviour (PR= 7.597, 95% CI: 3.701 – 15.597). Conclusion: According to this study, diabetic patients with poor knowledge are at greater risk of having poor COVID-19 prevention behaviours. COVID-19 prevention programs, especially health education programs at the community health centre, need to be improved to ensure that diabetic patients adopt reasonable and appropriate COVID-19 prevention practices.